The main provisions of the legal regulation of the public procurement system in the European Union (Journal of actual problems of jurisprudence, 2021)
The article presents the general characteristics and peculiarities of the legal regulation of public procurement within the European Union. Public procurement is extremely important both for European integration and for states as a whole due to the fact that it is a significant sector of the economy. To date, the issue of legal regulation of public procurement is relevant throughout the world, and the direct subject is the state itself, which is interested in their maximum efficiency. The purpose of the authors is to conduct a legal analysis of the EU Directives, as well as international treaties to which this integration association is a party, establishing common standards and norms in the field of regulation of public procurement. While carrying out this research the authors used such general scientific methods as method of scientific abstraction, qualitative expert assessment, quantitative assessment and structural analysis. The theoretical significance of the study consist of the fact that the work provides theoretical conclusions that can be used in scientific and practical developments on the problematic issues raised. In conclusion, the authors notes the effectiveness of the European system of organization of public procurement, implemented on the basis of its principles and approaches, which make it possible to form effective national systems of public procurement, corresponding to the world standards. Key words: public procurement, legal regulation, efficiency of public procurement system, European Union, World Trade Organization.